2021
DOI: 10.22244/rheedea.2021.31.03.12
|View full text |Cite
|
Sign up to set email alerts
|

Mycaranthes latifolia (Orchidaceae), a new record for Vietnam

Abstract: Mycaranthes latifolia Blume, distributed from Peninsular Malaysia, Borneo, Sumatra to Java is now reported for the first time in Vietnam. A morphological description, colour plate and line drawings, information on habitat and phenology are provided. An identification key to the species of Mycaranthes in Vietnam is also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Dendrobium is one of the largest genera in the flowering family Orchidaceae, with more than 1500 species, mostly found in Asia and Australia . Several species of Dendrobium plants have been used as traditional medicines in China, India, and Southeast Asia for treatment of skin disorders, reducing fever, headache and stomachache, and promoting body fluids. , Dendrobium crumenatum Sw. (Thai name Wai Tamoi) is an epiphytic plant that is distributed around Southeast Asia (Thailand, Philippines, Indonesia), India, and Hawaii. D. crumenatum has been used in traditional medicine as juices for treatment of earache and a poultice for curing boils and pimples . Extracts from D. crumenatum exhibited potential antimicrobial activity .…”
mentioning
confidence: 99%
“…Dendrobium is one of the largest genera in the flowering family Orchidaceae, with more than 1500 species, mostly found in Asia and Australia . Several species of Dendrobium plants have been used as traditional medicines in China, India, and Southeast Asia for treatment of skin disorders, reducing fever, headache and stomachache, and promoting body fluids. , Dendrobium crumenatum Sw. (Thai name Wai Tamoi) is an epiphytic plant that is distributed around Southeast Asia (Thailand, Philippines, Indonesia), India, and Hawaii. D. crumenatum has been used in traditional medicine as juices for treatment of earache and a poultice for curing boils and pimples . Extracts from D. crumenatum exhibited potential antimicrobial activity .…”
mentioning
confidence: 99%
“…This plant is an epiphytic orchid (size 40-100 cm) with pseudobulbs. The flower is 3-4 cm, white, having white three sepals and two petals with yellow disc on the lip (Meesawat & Kanchanapoom, 2007;Ram et al, 2015). However, the phytochemical studies and biological activities of this plant have not been reported.…”
Section: Dendrobium Crumenatum Swmentioning
confidence: 99%
“…Several species of Dendrobium plants have been used as traditional medicines in China, India, and Southeast Asia for treatment of skin disorders, reducing fever, headache and stomachache, and promoting body fluids (Wang, 2021a(Wang, , 2021b. Dendrobium crumenatum Sw. (Thai name Wai Tamoi) is an epiphytic plant that is distributed around Southeast Asia (Thailand, Philippines, Indonesia), India, and Hawaii (Meesawat et al, 2008;Ram et al, 2015;Vaddhanaphuti, 2005). D. crumenatum has been used in traditional medicine as juices for treatment of earache and a poultice for curing boils and pimples (Wiart, 2012).…”
Section: Immunomodulatory Effects Of New Phenanthrene Derivatives Fro...mentioning
confidence: 99%